PENDAMPINGAN TATA KELOLA KEUANGAN DAN PEMASARAN BERBASIS DIGITAL DALAM MENINGKATKAN PENJUALAN - Nurwahyuni Syahrir; Muhammad Ihsan Ansari; Indra Basir (Universitas Mataram, 2023)
Renggeang Village is one of the villages that produce the most silkworms in Polewali Mandar Regency. However, raising silkworms is not very popular among people in Polewali Mandar Regency, West Sulawesi. Even though it has been established for more than 9 years, the main obstacle faced is the lack of understanding of recording financial reports, the business is still on the Home Industry scale, business capital is limited, product marketing is still carried out by word of mouth so production is still Pre Order. Community Service activities aim to provide training and assistance on financial governanc. and digital-based marketing Training and assistance in the form of preparing simple financial reports and digital marketing (social media and e-commerce). The method of implementing community service is training and mentoring with a chronological strategy. Stages The method of implementing this service is identifying problems, analyzing needs and solutions, training and mentoring involving all members of farmer groups, and monitoring evaluations to monitor and assist farmer groups The implementation of community service for the Renggeang Mandiri Farmer Group has gone well and received a positive response from all group members. It is hoped that proper implementation of training and mentoring activities will encourage Renggeang Mandiri Farmer groups to prepare financial reports and market their products by utilizing digital media platforms. The results expected to be obtained from this service are increased sales of Renggeang Mandiri Farmer Group products, increased digital technology skills, increased understanding of good financial governance. Therefore these results are expected to have an impact on the economic welfare of the Renggeang Mandiri Farmer Group. The implementation of community service has gone well with a positive response from partners. The implementation of community service is expected to increase the income and welfare of partners.